THE CURRENT STATUS OF IRON MINERALS IN INDONESIA - Siti Rochani; SARIMAN SARIMAN; Rezky Iriansyah Anugrah; Pramusanto Pramusanto (Puslitbang tekMIRA, 2008)
Indonesia has great iron mineral resources, comprising primary iron ore (17 %), iron sand (8 %) and lateritic iron ore (75 %). Nowadays, Indonesia’s primary iron (hematite, magnetite) has not been em- powered yet, due to the scattered area of the resources location. Meanwhile, national iron sand is commonly used for cement industries and its potency has not supported national steel industries yet because of low iron content (45-48 %). However there is an opportunity to be processed by using Ausmelt process technology. At present, lateritic iron ore is being used as coal liquefaction catalyst in the form of limonite, but hydrometallurgy would be a promising solution to beneficiate lateritic iron ore for steel industries.